Cardiac helical CT involving a low-radiation-dose protocol with a 100-kVp setting: Usefulness of hybrid iterative reconstruction and display preset optimization. Issue 46 (November 2016) - Iyama, Yuji; Nakaura, Takeshi; Yokoyama, Koichi; Kidoh, Masafumi; Yamashita, Yasuyuki
Abstract : Abstract: To compare the radiation dose and image quality of retrospective electrocardiogram (ECG)-gated cardiac computed tomography (CT) between a 100-kVp protocol, hybrid iterative reconstruction (HIR), and display preset optimization and the 120-kVp protocol. We prospectively enrolled 100 patients with tachycardia or atrial fibrillation scanned retrospective ECG-gated cardiac CT. We randomly assigned 50 patients to the 120-kVp protocol and 50 patients to the 100-kVp protocol. We compared effective doses (EDs) between the two protocols. The 120-kVp images were post-processed using filtered back projection (FBP). The 100-kVp images were post-processed using FBP (100-kVp protocol) and HIR (i-100-kVp protocol). We compared attenuation of the ascending aorta, signal-to-noise ratio (SNR), and image noise between the 120-kVp, 100-kVp, and i-100-kVp protocols. We performed qualitative image analysis for the 120-kVp and i-100-kVp protocols. ED of the 100-kVp protocol (4.4 ± 0.4 mSv) was 76% lower than that of the 120-kVp protocol (18.4 ± 0.6 mSv). Attenuations of the 100-kVp (549.1 ± 73.8 HU) and i-100-kVp (550.5 ± 73.7 HU) protocols were higher than that of the120-kVp protocol (437.3 ± 55.7 HU). Image noise of the 100-kVp (53.6 ± 18.5 HU) and i-100-kVp (30.9 ± 8.6 HU) protocols were higher than that of the120-kVp protocol (23.8 ± 5.7 HU). There was no significant difference in SNR and the result of qualitative image analysis between the 120-kVp and i-100-kVp protocols. The 100-kVp protocol with HIR reduced the 76% radiation dose while preserving the image quality compared with the conventional 120-kVp protocol on retrospective ECG-gated cardiac CT.